Evaluation of quality of services (QoS) of satellite-based data delivery system. - Panna, Dey. (2008)
The paper identifies the technical issues on latency and delay, which affect the delivery of IP data over satellite link and the perceived problems of the end users. Various QoS parameters were observed for SCPC and IP-DVB technologies, including Simplex and Duplex satellite links. It was observed that IP-DVB links were saturated compared to the SCPC links, thus affecting the throughput performance of IP-DVB links.